RELATIONSHIP BETWEEN DEMOGRAPHIC AND ENVIRONMENTAL FACTORS AND KNOWLEDGE OF SECONDARY SCHOOL STUDENTS ON NATURAL DISASTERS - Vladimir M. Cvetković; Jelena Stanišić (Zbornik Radova: Geografski institut "Jovan Cvijić", 2015)
The subject of quantitative research is to examine the connection between demographic (gender, age) and environmental factors (family, school and media) and knowledge and perceptions of students about natural disasters. Bearing in mind the orientation of the research design on determination of character and strength of relationships of demographic and environmental factors with the knowledge and perceptions of students about natural disasters, research has explicative goal. The authors use the method of interviewing high school students to identify demographic and environmental factors associated with the knowledge and perceptions of students about natural disasters. The study included 3,063 students of secondary schools in the city of Belgrade. Results suggest the existence of links between gender, success achieved in school and education of parents and the knowledge of students about natural disasters. The results also indicate that the education of students at school and within family does not affect the knowledge, but affects their perception on natural disasters. Bearing in mind the geographical space of Serbia, the study is based only on the Belgrade region, so the findings can be generalized only to the population of students in this area. Research findings indicate potential ways to influence students to raise level of knowledge about natural disasters to a higher level. Given the evident lack of education about natural disasters in Serbia, the study results can be used for policies of educational programs, which would contribute to improving the safety of youth culture.